2017
DOI: 10.1039/c7dt01529a
|View full text |Cite
|
Sign up to set email alerts
|

Primary photochemical processes for Pt(iv) diazido complexes prospective in photodynamic therapy of tumors

Abstract: A case study of chain photoaquation of mixed-ligand Pt(iv) diazido complexes tested in PDT of tumors is performed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…More recently, Shushakov et al. investigated the photophysical and photochemical processes of cis,trans,cis ‐[Pt(N 3 ) 2 (OH) 2 (NH 3 ) 2 ] and trans,trans,trans ‐[Pt(N 3 ) 2 (OH) 2 (NH 3 ) 2 ] on ps and μs timescales, capturing multistage photolysis for both complexes including initial substitution of one azide by a solvent molecule 19. Overall, the present findings by TEAS open up a new path for more comprehensive ultrafast photodynamic and high‐level theory studies of 1 , which are outside the scope of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Shushakov et al. investigated the photophysical and photochemical processes of cis,trans,cis ‐[Pt(N 3 ) 2 (OH) 2 (NH 3 ) 2 ] and trans,trans,trans ‐[Pt(N 3 ) 2 (OH) 2 (NH 3 ) 2 ] on ps and μs timescales, capturing multistage photolysis for both complexes including initial substitution of one azide by a solvent molecule 19. Overall, the present findings by TEAS open up a new path for more comprehensive ultrafast photodynamic and high‐level theory studies of 1 , which are outside the scope of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…[90][91][92][93] A recent study on the first stage of photodecomposition using ultrafast kinetic spectroscopy and nanosecond laser flash photolysis suggested that the photodecomposition of both cis 2 and trans 3 is a chain process beginning with the replacement of one azide ligand by a water molecule and the release of azidyl radicals. 94 Two successive Pt(III) intermediates participated in chain initiation and [Pt III (NH 3 ) 2 (OH) 2 ] + was a chain carrier. 95 In addition, [Pt(N 3 ) 3 (OH)(NH 3 )(Py)] was observed by LC-MS as a photosubstitution product of 6 as well as azide ions, indicating the release of azide ligands.…”
Section: Photodecomposition Pathwaysmentioning
confidence: 99%
“…Platinum­(IV) complexes, and in particular Pt­(IV) azides, , count among the first and yet most promising photoactivated drug candidates because they are stable in the absence of light and only upon light irradiation release highly cytotoxic products. Accordingly, their photoreaction pathways have been heavily investigated experimentally ,, but less so computationally. Thus, understanding the major photoreaction pathway at the atomic leveli.e., the dissociation of the azide ligands that recombine to nitrogen along with the reduction of the metal center to Pt­(II)remains elusive.…”
mentioning
confidence: 99%